Lingkungan Kerja Dan Motivasi Kerja Karyawan Hotel Matahari Beach Resort & Spa. - Swandini, Luh Putu Erik (Prospek: Jurnal Manajemen dan Bisnis, 2020)
This study aims to examine the effect of work environment and motivation towards employee performance at Matahari Beach Resort & Spa Hotel. Research design used in this study is quantitative causal. The research subjects were 122 employee who worked at Matahari Beach Resort & Spa Hotel and the objects in this study were work environment, work motivation and employee performance. Data collected through questionnaire and analyzed using path analysis. The results showed that: (1) work environment has a positive and significant affect on employee performance (2) work motivation has a positive and significant affect on employee performance (3) work environment has a positive and significant affect on work motivation and (4) work environment has a positive and significant effect on employee performance through work motivation at Matahari Beach Resort & Spa Hotel